2016
DOI: 10.1093/femspd/ftw052
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation ofin vitrohuman macrophage models for mycobacterial infection study

Abstract: Macrophages are phagocytic cells that play a key role maintaining the homeostasis of many tissues. Their function is essential for controlling and eradicating infecting mycobacteria. Human monocytic cell lines such as THP-1 and U937 have provided interesting insights into how mycobacteria subvert the host cell response. However, immortalized cell lines could bring some disadvantages. Here we compare the response of THP-1 and U937 cell lines with human monocyte-derived macrophages (hMDMs) to determine functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…To examine the molecular mechanism of TNT-induced cell death, we used the human macrophage cell line THP-1 as an infection model (Mendoza-Coronel and Castañón-Arreola, 2016; Riendeau and Kornfeld, 2003). Mtb strains (Table S1) secreting functional TNT replicated and increased cell numbers by 10- to 30-fold after 3–5 days, whereas the Δ cpnT deletion mutant did not replicate and was slowly killed (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the molecular mechanism of TNT-induced cell death, we used the human macrophage cell line THP-1 as an infection model (Mendoza-Coronel and Castañón-Arreola, 2016; Riendeau and Kornfeld, 2003). Mtb strains (Table S1) secreting functional TNT replicated and increased cell numbers by 10- to 30-fold after 3–5 days, whereas the Δ cpnT deletion mutant did not replicate and was slowly killed (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Immortalized cell lines are routinely used due to their availability in large scale, but they often originate from tumors and/or were obtained through multiple passages; thus, their genetic background is not well defined and their phenotype can vary between lots. As such, they may not always be appropriate models to understand tissue-specific cellular functions ( 12 , 13 ), or to correctly summarize critical interactions with pathogens, as reported in the case of Leishmania ( 14 ), adeno-associated virus ( 15 ), and Mtb ( 16 , 17 ). In this context, the large-scale availability of MPI cells as a primary cellular model mimicking lung AMs could open new prospects in the understanding of pulmonary diseases, notably those involving complex host-pathogen interactions like TB.…”
Section: Introductionmentioning
confidence: 99%
“…Several macrophage models have been used to study M. tuberculosis infection. These include primary macrophages, mainly human monocyte-derived macrophages (hMDMs) or mouse bone marrow-derived macrophages (BMDMs); and cell lines, such as the human THP-1 and U937, or the murine J774 and RAW 264.7 4 5 . BMDMs are a useful model because they can be easily cultured and expanded to large numbers.…”
mentioning
confidence: 99%
“…Previous comparisons of macrophage infection models for M. tuberculosis have focused on certain phenotypic traits such as intracellular growth, cytokine production, or phagosome characteristics 5 9 10 . Jordao and collaborators found that Mycobacterium bovis grows more efficiently in hMDMs than in J774 over a 7-day time course, even though both types of macrophages can restrict growth during the first 24 hours of infection through a mechanism involving phagosome acidification and nitric oxide production 9 .…”
mentioning
confidence: 99%